(untitled) (International Journal of Engineering and Computer Science, 2017)
Now a day’s use of internet is increasing rapidly. For broad topic each new user may have his different user goals. Hence the inference and analysis of the user search goals can improve the efficiency of the search engine and also reduce the time needed to search the query as unwanted data can get hide from the user and user get only his goal oriented search results. Currently everyone is searching on the internet and internet provides you ambiguous result of same things as it contains lot of information. In proposed method system will provide the information related to the user goals. In this paper we have discover a novel framework to discover the user goals by clustering the user search goals and then new approach to generate the pseudo document to represent the clustering effectively. At the end we have proposed novel approach CAP to calculate the performance of the search engine.